Effectiveness of a dedicated small bowel neoplasia screening program by capsule endoscopy in Lynch syndrome: 5 years results from a tertiary care center. (July 2020) - Perrod, Guillaume; Samaha, Elia; Perez-Cuadrado-Robles, Enrique; Berger, Arthur; Benosman, Hedi; Khater, Sherine; Vienne, Ariane; Cuenod, Charles-André; Zaanan, Aziz; Laurent-Puig, Pierre; Rahmi, Gabriel; Cellier, Christophe
Background and aims: The role of small bowel neoplasia (SBN) screening in asymptomatic patients with Lynch syndrome (LS) is uncertain. The aim of our study was to assess the effectiveness of screening by capsule endoscopy (CE) in these patients. Methods: This study was an observational, analytical, and retrospective single-center study within the PRED-IdF network. All consecutive asymptomatic patients older than 35 years-old with confirmed LS and no personal history of SBN who started the screening from 2010–2015 were included. The baseline screening and 24 months follow-up were performed by CE. The CE diagnostic yield (positive tumor or polyp) and accuracy, using the follow-up as gold standard, were evaluated. Results: A total of 150 patients underwent the SBN screening program and 135 (52.7 ± 11.2 years-old, 37.8% male) met the inclusion criteria. The baseline CE diagnostic yield was 4.4% (3 polyps, 3 tumors) and the proximal small bowel was the most common location ( n  = 4, 66.7%). In total, 87 patients underwent follow-up and the diagnostic yield was 4.6%. Four patients were considered positive at follow-up (2 adenomas, 2 adenocarcinomas). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of CE were 60%, 100%, 100%, 96.9%, and 97%, respectively. Conclusions: CE is an accurate procedure for baseline screening of SBN in LS patients and may be efficient for follow-up procedures. However, the optimal starting age of screening and intervals of follow-up must be clarified.